Numerical simulation and factor analysis of petrochemical pipe erosion-corrosion failure. Issue 1 (May 2016) - XU, G F; OU, G F; Chen, T; Li, P X; JIN, H Z
Abstract: Based on the behavior of carbon steel outlet tube in REAC pipes of Zhenhai Refining & Chemical Company, the mathematical model of fluid-solid interaction was established according to the mechanism of erosion-corrosion damage. The interaction between corrosion products protecting film and multiphase liquid was analyzed by numerical simulation method. The distribution of shearing stress on the inwall of elbow bend, and the distribution of principal displacement, stress and strain of corrosion products protecting film were disclosed, while the erosion-corrosion failure processes was studied. The simulation result coincides with that of the positioned thickness gauging which validated the reliability and feasibility of the finite element analysis software simulation method. The obtained results can be used in the erosion-corrosion failure analysis, structural optimization, in-service testing positioning, life prediction, risk assessment, safety and other security projects for multiphase flow pipeline.